Gambaran Spasial Hubungan antara Faktor Lingkungan dan Ekonomi dengan Stunting Balita di Provinsi Nusa Tenggara Timur - Nashriyah, Siti Fadhilatun; Makhful, Martya Rahmaniati; Devi, Yuli Puspita (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2023)
Background: The President through Presidential Regulation Number 72 of 2021 is committed to accelerating the reduction of stunting in Indonesia. The stunting priority areas also continue to be increased from year to year. In Indonesia, East Nusa Tenggara Province is the province with the highest prevalence of stunting, namely 37.8% in 2021. Objective: To find out the spatial picture and the correlation between environmental factors and economic factors with the prevalence of stunting in East Nusa Tenggara Province in 2021. Methods: The research design is an ecological study with a spatial approach. This study uses secondary data in the form of reports issued by the Indonesian Ministry of Health (SSGI: Indonesian Nutritional Status Study) and the BKKBN (PK: Family Data Collection) in 2021 with district/city-level analysis units in East Nusa Tenggara Province. Data analysis used a correlation test and mapping was carried out using the QGIS 2.8.1 application. Results: The prevalence of stunting in NTT Province tends to be high in the eastern part while the risk factors for stunting (unfavorable environment and economy) tend to be high in the western part. The correlation test showed that the correlation between the prevalence of stunting and the poor was 0.165 (p = 0.463); with inadequate latrines of 0.420 (p = 0.052); and with inadequate drinking water sources of 0.426 (p = 0.048).